2019
DOI: 10.1111/ggi.13661
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pathogens and mortality predictors of older Chinese patients with nosocomial urinary tract infections

Abstract: Aim:The aim of the present study was to investigate predominant pathogens and predictors of 28-day mortality of older Chinese patients with nosocomial urinary tract infections (NUTI). Methods:We retrospectively studied 1122 older patients (aged ≥60 years) with culture-. The clinical features, microbial distributions and outcomes of these patients were recorded and compared between survival and death patients. Multivariate logistic regression was carried out to identify independent predictors of 28-day mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…Усиление колонизации мочевых путей грибами происходит при наличии мочевого дренажа, конкремента в мочевых путях и после антибактериальной терапии [4,10,12,16,35]. Однако влияние антибактериальной терапии как единственного фактора риска усиления колонизации грибами Candida у женщин с неосложненной ИМП не подтвердилось в исследовании R.M.…”
Section: факторы риска кандидоза мочевыводящих путейunclassified
See 2 more Smart Citations
“…Усиление колонизации мочевых путей грибами происходит при наличии мочевого дренажа, конкремента в мочевых путях и после антибактериальной терапии [4,10,12,16,35]. Однако влияние антибактериальной терапии как единственного фактора риска усиления колонизации грибами Candida у женщин с неосложненной ИМП не подтвердилось в исследовании R.M.…”
Section: факторы риска кандидоза мочевыводящих путейunclassified
“…Пребывание больного в отделении реанимации и интенсивной терапии является независимым фактором риска развития мочевой инфекции, вызванной Candida spp. [4,16,35]. По данным W. Hu et al, у пациентов в возрасте старше 65 лет с кандидурией повышенный индекс коморбидности Чарлсона, снижение уровня преальбумина и повышение уровня С-реактивного белка должны рассматриваться как дополнительные факторы риска повышенной летальности [16].…”
Section: факторы риска кандидоза мочевыводящих путейunclassified
See 1 more Smart Citation
“…A retrospective study reported that urinary tract infection contributed to high 28-day mortality rate in hospitalized Chinese older patients [31]. Catheter-associated urinary tract infection was also accompanied by an increase in mortality [32].…”
Section: Associated Risk Factors In Hospitalized Bedridden Patientsmentioning
confidence: 99%
“…Common pathogens involved are Escherichia coli, Klebsiella spp., Mycoplasma spp., Enterobacter spp., Staphylococcus aureus, Candida albicans, and worms like threadworms, flukeworms, etc. Of these, E. coli is the most common cause of UTI [13,14].…”
Section: Introductionmentioning
confidence: 99%